Amyloid PET imaging in clinical practice. Issue 6 (24th September 2020) - Kolanko, Magdalena A; Win, Zarni; Loreto, Flavia; Patel, Neva; Carswell, Christopher; Gontsarova, Anastassia; Perry, Richard J; Malhotra, Paresh A
Abstract : Amyloid positron emission tomography (PET) imaging enables in vivo detection of brain Aβ deposition, one of the neuropathological hallmarks of Alzheimer's disease. There is increasing evidence to support its clinical utility, with major studies showing that amyloid PET imaging improves diagnostic accuracy, increases diagnostic certainty and results in therapeutic changes. The Amyloid Imaging Taskforce has developed appropriate use criteria to guide clinicians by predefining certain scenarios where amyloid PET would be justified. This review provides a practical guide on how and when to use amyloid PET, based on the available research and our own experience. We discuss its three main appropriate indications and illustrate these with clinical cases. We stress the importance of a multidisciplinary approach when deciding who might benefit from amyloid PET imaging. Finally, we highlight some practical points and common pitfalls in its interpretation.